Seasonal and long-term climate drivers of tree species phenology and litterfall in a Nothofagus cool temperate rainforest of Australia - Vogado, Nara O.; Liddell, Michael J.; Peacock, Ross J. (Frontiers in Ecology and Evolution, 2024)
The cool temperate rainforests of eastern Australia are at risk from anthropogenic climate change with predicted changes in temperature, rainfall, severe weather, basal cloud layer and droughts. Phenology and litter production are fundamental reproductive and growth processes to document in any ecosystem, yet very few long-term studies exist in Australian rainforests. In this study, long-term data sets are used to describe different phenological and litter production behaviours of tree species in a Nothofagus cool temperate rainforest in New South Wales (NSW), Australia, analysing seasonal and inter-annual climate drivers. Leaf fall at community level was mostly influenced by Nothofagus moorei, driven by temperature and wind speed, and Ceratopetalum apetalum, driven by temperature, rainfall and solar radiation.Mean dates of leaf fall at community level were found to be advancing, correlated with an advance of solar radiation. We also analysed in detail the flowering behaviour of the dominant canopy tree species, Nothofagus moorei, which masts with a mean inter-flowering period of 3-4 years in 65% of flowering events. Three of the studied species presented mast flowering, Ceratopetalum apetalum, Nothofagus moorei, and Orites excelsus, however, they did not mast in the same years. All species presented strong seasonality in their phenological activity, but seasonality peaked in different months, and were driven by varied climate variables. Supraannual peaks of flowering and fruiting did not occur at the same time for all species, and climate drivers of inter-annual phenological behaviour were different for each species. Our results show that projected changes in climate will affect species from cool-temperate rainforests differently, not only affecting biomass production, but also species reproductive output and forest dynamics.